A scientific future shared with AI. - Renee Hoch; Joanna Clarke (PLoS Biology)
Artificial intelligence (AI) tools now exist to aid almost every aspect of the research process, from hypothesis generation and data analysis to manuscript drafting and publication. What does the future hold for researchers and publishers as AI use continues to increase?